Immunopathogenesis of Different Emerging Viral Infections: Evasion, Fatal Mechanism, and Prevention - Yang, Betsy; Yang, Kuender D. (Frontiers in Immunology, 2021)
Different emerging viral infections may emerge in different regions of the world and pose a global pandemic threat with high fatality. Clarification of the immunopathogenesis of different emerging viral infections can provide a plan for the crisis management and prevention of emerging infections. This perspective article describes how an emerging viral infection evolves from microbial mutation, zoonotic and/or vector-borne transmission that progresses to a fatal infection due to overt viremia, tissue-specific cytotropic damage or/and immunopathology. We classified immunopathogenesis of common emerging viral infections into 4 categories: 1) deficient immunity with disseminated viremia (e.g., Ebola); 2) pneumocytotropism with/without later hyperinflammation (e.g., COVID-19); 3) augmented immunopathology (e.g., Hanta); and 4) antibody-dependent enhancement of infection with altered immunity (e.g., Dengue). A practical guide to early blocking of viral evasion, limiting viral load and identifying the fatal mechanism of an emerging viral infection is provided to prevent and reduce the transmission, morbidity and mortality of an emerging viral infection.